Amino acid based imidazolium zwitterions as novel and green corrosion inhibitors for mild steel: Experimental, DFT and MD studies - Srivastava V.; Haque J.; Verma C.; Singh P.; Lgaz H.; Salghi R.; Quraishi M.A. (My University, 2025)
Three novel amino acids based corrosion inhibitors namely 2-(3-(carboxymethyl)-1H-imidazol-3-ium-1-yl)acetate (AIZ-1), 2-(3-(1-carboxyethyl)-1H-imidazol-3-ium-1-yl)propanoate (AIZ-2) and 2-(3-(1-carboxy-2-phenylethyl)-1H-imidazol-3-ium-1-yl)-3-phenylpropanoate (AIZ-3) were synthesized by condensing glyoxal, formaldehyde and amino acids, and characterized. The corrosion inhibition performance of synthesized inhibitors was studied by electrochemical impedance (EIS) and potentiodynamic polarization (PDP) methods. Among the studied inhibitors, AIZ-3 showed the maximum inhibition efficiency (IE) of 96.08% at a concentration as low as 0.55 mM (200 ppm). The results of potentiodynamic study reveal that AIZ-1 acts as cathodic inhibitor while AIZ-2 and AIZ-3 act as mixed type inhibitors. The results of EIS studies showed that in the presence of inhibitors, polarization resistance increased and Cdl decreased due adsorption of inhibitors at the metal surface. The adsorption of AIZs on the mild steel surface followed the Langmuir adsorption isotherm. The result of scanning electron microscope (SEM), atomic force microscope (AFM) and energy-dispersive X-ray spectroscopy (EDX) supported the formation of inhibitors film on the metal surface. The quantum chemical parameters and molecular dynamics (MD) simulations were used to study the reactivity and adsorption behavior of zwitterions. The results of the theoretical investigation and experimental studies well complimented each other. © 2017